National Institutes of Health R-series Grants portfolio of racism and healthcare, 2017-2022 - Judith Aponte; Maria Isabel Roldós (BMC, 2023)
Abstract Background Any form of racism in healthcare is an unacceptable barrier to receiving equitable and quality care, further contributing to health disparities among populations. For these reasons, it is critical to have a better understanding on the amount of research and scientific advances of funded projects aimed at racism in healthcare. An examination of the distribution of R-series funded research by the National Institutes of Health (NIH) on racism in healthcare during a 5-year fiscal year (FY) period (2017-2022) was conducted by the study team. Methods This cross-sectional study used publicly available data from the NIH RePORTER (Research Portfolio Online Reporting Tools: Expenditures and Results) for research project grants awarded on racism and healthcare during the FYs of 2017 to 2022. The number of R-series NIH funded projects on racism in healthcare were examined, including the abstract and public health relevance statement, number of publications, spending category, fiscal start and end dates, total amount of funding each year, funding agency/center(s), and type of funding opportunity announcements. Descriptive statistics were performed on the data by the research team. Results There were a total of 93 R-series grants funded during the FYs of 2017 to 2022. Most of the grants were R01s (77.4%); focused primarily on racism at the system-wide level (68.8%), and on patients (64.5%); the largest racial and ethnic minority group reported were African/American/Black (20.4%); and close to 40% did not report race or ethnicity. None of the grants focused in internalized racism, which is at the individual -level. From the FYs of 2017 to 2022, 0.07% of all NIH research funding was awarded to racism in healthcare. Conclusion The findings of this study showed the need for continued funding and of the need of more research on racism in healthcare, that potentially can reduce health disparities and inequities.